Spring onion (Allium fistulosum L.) farmer’s system typologies of Maracaibo municipality, Zulia State, Venezuela - Albornoz, Arlenis; Urdaneta, Fátima (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2025)
In Venezuela, spring onions are the most widely consumed edible leafy vegetable. Their production is concentrated in small settlements where the interaction of farmers with social, technical, economic, environmental, and territorial factors gives rise to a different types of production systems. The study aimed to typify the spring onion production systems in the municipality of Maracaibo, Zulia state, Venezuela. A sample of 53 farmers was considered, to whom was applied a structured questionnaire with sociodemographic, labor, technology, territory, natural environment, and socioeconomic enviroment information. The groups were formed using multivariate techniques (Principal Components and K-Means Clustering) and were compared using Chi-square. The four groups were: 1. Mixed Family Production Systems (MFS = 36 % of the sample), centered on family labor, that combined agricultural crops with small-scale animal husbandry and the use of organic fertilizer. 2. Intensive technology systems (ITS = 23 %), where chemical fertilizers (nitrogen and phosphorus) were used intensively. 3. Family polyculture systems (SPF = 28 %) cultivated spring onion and other crops (cilantro, cassava, and plantain) for commercial sales. 4. Technified polyculture systems (SPT = 13 %), which were labor-intensive, planted large areas of spring onions and other crops (plantain and “topocho”), performed a more efficient use of inputs, and pests control. These findings help to understand specificities of each typology, that allow personalized implementation of agricultural development strategies, addressing specific factors for each group.